De novo 2q36.1q36.3 interstitial deletion involving the PAX3 and EPHA4 genes in a fetus with spina bifida and cleft palate. Issue 6 (18th April 2014) - Goumy, Carole; Gay‐Bellile, Mathilde; Eymard‐Pierre, Eléonore; Kemeny, Stephan; Gouas, Laetitia; Déchelotte, Pierre; Gallot, Denis; Véronèse, Lauren; Tchirkov, Andrei; Pebrel‐Richard, Céline; Vago, Philippe
<x xml:space="preserve">Abstract</x> Background Interstitial 2q36 deletion is a rare event. Only two previously published cases of 2q36 deletions were characterized using array‐CGH. This is the first case diagnosed prenatally. Methods We report on the prenatal diagnosis of a 2q36.1q36.3 interstitial deletion in a fetus with facial dysmorphism, spina bifida, and cleft palate. Results Array‐CGH analysis revealed a 5.6 Mb interstitial deletion of the long arm of chromosome 2q36.1q36.3, including the PAX3 and EPHA4 genes. Conclusion The present study reinforces the hypothesis that PAX3 haploinsufficiency may be associated with neural tube defects in humans and suggests that the EPHA4 gene might be implicated during palate development. This report also illustrates the added value of array‐CGH to detect cryptic chromosomal imbalances in malformed fetuses and to improve genetic counseling prenatally. Birth Defects Research (Part A) 100:507–511, 2014. © 2014 Wiley Periodicals, Inc.